(untitled) (Iranian Journal of Kidney Diseases, 2010)
Posttransplant lymphoproliferative disorder (PTLD) is a well-documented complication that arises as a result of immunosuppression in the setting of solid organ or bone marrow transplantation. The disorder may be subtle and/or extranodal. We report a patient with extranodal lymphoma following kidney transplantation who had successful treatment with surgery and chemotherapy.